Genetic variability of Colletotrichum sublineolum through ISSR markers (Research, Society and Development, 2021)
The occurrence of diseases is a limiting factor in the development of sorghum crop. Among the diseases that causes losses in sorghum production, anthracnose is the main and most severe, mainly by the genetic variability of the pathogen. In this context, the aim of this study was to evaluate the genetic variability of Colletotrichum sublineolum isolates. DNA were extracted from 56 monosporic isolates of C. sublineolum using a DNA extraction kit, and to perform the analysis of genetic diversity of the isolates were used ISSR primers. After amplification, it was determined the polymorphic information content (PIC), allelic frequency, UPGMA and Tocher clustering analyzes and, using software Structure, the genetic structure. According to the descriptive analysis of the genetic variability of C. Sublineolum isolates, primer AP1 presented the higher value of polymorphic information content (PIC). The higher allelic frequency was observed in loci 06, 09, 10, and 24, and the lowest in locus 02. As for the clustering method, it was observed a tendency of grouping C. sublineolum isolates according the geographic origin and, in addition to demonstrating the genetic variability between the C. sublineolum isolates, it was observed the occurrence of introgression among the isolates.